THE PERSUASIVE TECHNIQUE TYPES IN DONALD TRUMP’S PUBLIC SPEAKING - Ginting, Rizky Sakbanita Putri; Sili, Surya; Setyowati, Ririn (Fakultas Ilmu Budaya Universitas Mulawarman, 2019)
The area of this research is a discourse analysis of the use of persuasive technique types. The object as the background of the study is related to the president’s election, conducted in the USA. Donald Trump won the election and the majority of citizens in the USA chose him as President of the USA in 2016. It is surprised people because he raised the issues, which are very racist and anti-Islam. The public speaking by Donald Trump was reasonable to be studied and the way he talks that is clear and systematic becomes a reason by the researcher to study about the persuasive technique types used in his public speaking speech. This research focused on identifying the types of the persuasive technique used in Donald Trump’s Public Speaking and finding the persuasive technique that is most frequently used by him through qualitative content analysis. The researcher found three types of persuasive technique that used in both of speech which is remarked on North Carolina and remarked on Springfield, Ohio. Those types are Logos, Ethos, and Pathos. The result of this research showed the types of the persuasive technique used in Donald Trump’s public speaking speech texts elaborated by primarily Pathos, Ethos, and followed by Logos. Pathos was 207 sentences found, Ethos was 164 sentences found, and Logos was 58 sentences found, total data of the study is 429. In addition, the researcher also found the persuasive technique type that is most frequently used by Donald Trump, it was Pathos. He frequently used Pathos to influence the voters and the audience. Penelitian ini adalah analisis wacana penggunaan jenis teknik persuasif. Objek sebagai latar belakang penelitian ini terkait dengan pemilihan presiden, yang dilakukan di AS. Donald Trump memenangkan pemilihan dan mayoritas warga di Amerika Serikat memilih dia sebagai Presiden Amerika Serikat pada tahun 2016. Ini mengejutkan orang-orang karena dia mengangkat isu-isu yaitu sangat rasis dan anti-Islam. Pembicaraan publik oleh Donald Trump masuk akal untuk dipelajari dan cara dia berbicara yang jelas dan sistematis menjadi alasan oleh peneliti untuk mempelajari tentang jenis teknik persuasif yang digunakan dalam pidato berbicara di depan umum. Penelitian ini berfokus pada identifikasi jenis teknik persuasif yang digunakan dalam pembicaraan publik Donald Trump dan menemukan teknik persuasif yang paling sering digunakan oleh dia melalui kualitatif konten analisis. Peneliti menemukan tiga jenis teknik persuasif yang digunakan dalam kedua pidato di North Carolina dan di Springfield, Ohio. Jenis-jenis persuasif teknik nya adalah Logos, Ethos, dan Pathos. Hasil penelitian ini menunjukkan jenis teknik persuasif yang digunakan dalam teks-teks pidato publik Donald Trump yang diuraikan adalah yang terutama Pathos, Ethos, dan diikuti oleh Logos. Pathos 207 kalimat ditemukan, Ethos 164 kalimat ditemukan, dan Logos adalah 58 kalimat ditemukan, total data penelitian adalah 429. Selain itu, peneliti juga menemukan tipe teknik persuasif yang paling sering digunakan oleh Donald Trump adalah Pathos. Dia lebih sering menggunakan Pathos untuk mempengaruhi pemilih dan penonton.